2013
DOI: 10.3892/or.2013.2624
|View full text |Cite
|
Sign up to set email alerts
|

Different regulatory pathways are involved in the proliferative inhibition of two types of leukemia cell lines induced by paclitaxel

Abstract: Abstract. Paclitaxel, one of the broadest-spectrum anticancer agents, is currently being used in the treatment of patients with solid tumors. In the present study, we compared the effect of paclitaxel on two types of leukemia cells. Our results showed that paclitaxel could inhibit the proliferation of MEL and K562 cells in a dose-and time-dependent manner. The mechanism of proliferative inhibition in K562 cells treated by paclitaxel was related to the cell cycle arrest in the G 2 /M phase, as well as the induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Paclitaxel exhibits a high antitumor efficacy and is able to suppress cancer cell proliferation through the inhibition of mitosis (17). The results of the present study demonstrated that A549 cell proliferation was markedly inhibited, in a time-dependent manner, by paclitaxel, which is consistent with previous studies (18). However, the rate of paclitaxel-induced growth inhibition was markedly decreased in A549-F10 cells compared with the negative control, suggesting that the overexpression of F10 inhibited chemosensitivity to paclitaxel in A549 lung cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…Paclitaxel exhibits a high antitumor efficacy and is able to suppress cancer cell proliferation through the inhibition of mitosis (17). The results of the present study demonstrated that A549 cell proliferation was markedly inhibited, in a time-dependent manner, by paclitaxel, which is consistent with previous studies (18). However, the rate of paclitaxel-induced growth inhibition was markedly decreased in A549-F10 cells compared with the negative control, suggesting that the overexpression of F10 inhibited chemosensitivity to paclitaxel in A549 lung cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…Apoptosis is a proactive cell death process in which cells undergo a certain stimulus to maintaining the stability of the internal environment, The morphological alterations of apoptosis are characterized by cell shrinkage, chromatin condensation, nuclear fragmentation, DNA degradation, and apoptotic body formation ( 27 ). Paclitaxel may arrest the division of cancer cells in the G 2 /M-phase and elevate the expression of cyclinB1 ( 28 , 29 ). In the present study, paclitaxel-treated CHMm cells exhibited morphological alterations characteristic of apoptosis, including cell shrinkage, intracellular vacuolization and chromatin condensation.…”
Section: Discussionmentioning
confidence: 99%
“…Propidium iodide (PI, BestBio biotechnologies, Shanghai, China) (10 μg/ml, 50 μl) or Hoechst 33342 (Beyotime Institute of Biotechnology, China; 10 μg/ml, 50 μl) was added. After incubation at room temperature for 5 minutes in the dark, image analysis was performed through an inverted fluorescence microscope (TE2000-U, Nikon, Tokyo, Japan) as described previously 36 37 .…”
Section: Methodsmentioning
confidence: 99%